(untitled) (Journal of the Bangladesh Association of Young Researchers, 2012)
Emerging epidemiological and intervention data support the connection between increased tomato consumption and reduced risk for cardiovascular disease. Tomato contains several antioxidants including lycopene, polyphenols, trace elements, and vitamins those are known to inhibit atherosclerotic processes. Recent studies have demonstrated that tomato also contains several potent anti-platelet compounds. The ingestion of these tomato components significantly affects ex vivo platelet function when supplemented in human volunteers. Platelet aggregation is a central mechanism in the pathogenesis of acute coronary syndromes, including myocardial infarction and unstable angina. Since tomato can reduce both platelet hyperactivity and atherosclerosis process thus makes it an ideal food for the cardiovascular system. Additionally tomato has the lowest content of uric acid than any fruits and vegetables. Tomato extract , commercially known as Fruitflow, is an absolutely unique dietary solution for cardiovascular support that works immediately after ingestion. Fruitflow works by helping to keep blood platelets smooth, thereby promoting healthy circulation and pressure within the cardiovascular system. DOI: http://dx.doi.org/10.3329/jbayr.v1i2.10027